Biologically Inspired, Cell‐Selective Release of Aptamer‐Trapped Growth Factors by Traction Forces. Issue 7 (7th January 2019) - Stejskalová, Anna; Oliva, Nuria; England, Frances J.; Almquist, Benjamin D.
Abstract: Biomaterial scaffolds that are designed to incorporate dynamic, spatiotemporal information have the potential to interface with cells and tissues to direct behavior. Here, a bioinspired, programmable nanotechnology‐based platform is described that harnesses cellular traction forces to activate growth factors, eliminating the need for exogenous triggers (e.g., light), spatially diffuse triggers (e.g., enzymes, pH changes), or passive activation (e.g., hydrolysis). Flexible aptamer technology is used to create modular, synthetic mimics of the Large Latent Complex that restrains transforming growth factor‐β1 (TGF‐β1). This flexible nanotechnology‐based approach is shown here to work with both platelet‐derived growth factor‐BB (PDGF‐BB) and vascular endothelial growth factor (VEGF‐165), integrate with glass coverslips, polyacrylamide gels, and collagen scaffolds, enable activation by various cells (e.g., primary human dermal fibroblasts, HMEC‐1 endothelial cells), and unlock fundamentally new capabilities such as selective activation of growth factors by differing cell types (e.g., activation by smooth muscle cells but not fibroblasts) within clinically relevant collagen sponges. Abstract : Harnessing cells' ability to pull on materials is unexplored for controlling the release of bioactive proteins. Aptamers are modified to create bioinspired nanostructures that activate proteins upon application of cellular traction forces, and integrate with virtually any biomaterial and fabrication workflow (e.g., 3D printing, photopatterning). Furthermore, this fundamentally new approach enables unique capabilities such as cell‐selective activation of proteins.